The Effect of Additional Employee Income Compensation on the Performance of State Civil Servant Employees at the Regional Secretariat of Gowa Regency - Mardiana Mardiana; Siti Aisyah; Sitti Marhumi (Pustaka Digital Indonesia, 2026)
The urgency of this study lies in evaluating how additional employee income compensation contributes to improving the performance of State Civil Servants and in providing insights for developing more effective compensation policies within the Regional Secretariat of Gowa Regency. This study aims to examine the effect of Additional Employee Income (Tambahan Penghasilan Pegawai/TPP) as a form of compensation on the performance of State Civil Apparatus (ASN) at the Regional Secretariat of Gowa Regency. The research adopts a quantitative approach using a causal associative design to identify the relationship between compensation and employee performance. Data were collected through structured questionnaires distributed to all 75 ASN employees using a saturated sampling technique. The collected data were analyzed using simple linear regression, supported by validity, reliability, and classical assumption tests to ensure the robustness of the model. The results indicate that compensation has a positive and statistically significant effect on employee performance, as evidenced by a t-value of 8.667 and a significance level of 0.000. Furthermore, the coefficient of determination (R²) shows that 50.7% of the variation in employee performance can be explained by compensation, while the remaining 49.3% is influenced by other factors. These findings highlight the critical role of financial incentives in enhancing employee productivity, responsibility, and work quality in the public sector. The study contributes to the literature on human resource management by providing empirical evidence from a regional government context, emphasizing that the effectiveness of compensation depends not only on its financial value but also on fairness, transparency, and consistency in implementation.